Resistencia a la compresión de carillas cerámicas de disilicato de litio cementadas con cemento resinoso dual y cemento resinoso dual autoadhesivo en premolares maxilares - Mellado Alfaro, Brando (2015)
ABSTRACT: The aim of this work was to establish the resistance degree to the compression force in porcelain laminate. In this experimental in vitro study 30 premolars were selected and randomly divided in groups of 15 teeth each, subsequently specimens were prepared for ceramic veneers 0.5 mm thick. The first group was cemented with dual resin cement (CRD) and the second with dual adhesive resin cement (CRDA). After cementation was tested in a universal test machine until fracture compression forces occurred (N) at 1 mm / min speed. Student´s t-test (a= 0.05) was used to compare means. The results showed statistically significant differences (p<0.05) between groups. The mean compressive strength for cemented samples was 677.47 N and 550.0 N for dual resin cement and auto-adhesive dual resin cement respectively. It was found that porcelain laminate veneers made of lithium disilicate and cemented with CRD have greater resistance to compression force compered to CRDA.